The Impact of Field Data Capturing Technologies on Automated Construction Project Progress Monitoring - Alizadehsalehi, Sepehr; Yitmen, İbrahim (Elsevier Science Bv, 2016)
Accurate and timely information of construction project progress in a regular repeated basis is one of the critical stages of construction management. The purpose of this study is to investigate the impact of field data capturing technologies (FDCT), in combination with building information modelling (BIM) on automated construction project progress monitoring (ACPPM). The research is based on a survey of contracting and engineering consulting firms operating in the Middle East, Mid-Asia, Europe, North America, and Far East. Based on an evaluation of the findings, 3D Laser Scanning (LS), Image-based, and Radio Frequency Identification (RFID) technologies in combination with BIM were found as the most used technologies for ACPPM. At the end, a conceptual framework is illustrated and managerial implications are highlighted with a sample statement focusing on requirements, processes and benefits. The study confirms the importance of using BIM-based FDCT in enhancing ACPPM factors performance. (C) 2016 The Authors. Published by Elsevier Ltd.
World Multidisciplinary Civil Engineering-Architecture-Urban Planning Symposium (WMCAUS) -- JUN 13-17, 2016 -- Prague, CZECH REPUBLIC
Keywords: field data capturing technologies; automated construction project progress monitoring; BIM